Increasing Knowledge Of Healthy Snacks And Hand Washing For Preschool Children Through Children's Song - Pujiastuti, Nurul; Retnowati, Lucia; Widiani, Esti; Hidayah, Nurul (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
The reasons behind snacking habits in children include children not having breakfast, children's psychology, biological needs, and parental behavior. One of the efforts to introduce healthy snacks to preschool children is through children's songs that can be sung every day so that children know about healthy snacks. The purpose of this community service is to increase the knowledge of preschool children about how to choose healthy snacks and the six steps of washing hands. This community service activity was carried out at the ABA Kindergarten, Sumberporong Village, Kec. Lawang Kab. Unfortunately and given to 14 children. The implementation of the activity consists of 3 (three) stages, namely assessment, education, and evaluation. The assessment stage is carried out by assessing children's knowledge about healthy snacks and the six steps of washing hands. The education stage is carried out through the method of singing songs about healthy snacks and six steps of washing hands with blackboard media to write song lyrics. The evaluation stage was carried out by asking children about their commitment to washing their hands with six steps and choosing healthy snacks. The results of community service activities showed that there was an increase in children's knowledge about the six steps of washing hands and choosing healthy snacks after being given education. The results of the evaluation showed that the children had a commitment and were willing to do the six steps of washing their hands and choosing healthy snacks. The activity of singing a song about the six steps of washing hands and choosing healthy snacks is carried out every day at the beginning of the meeting so that children memorize and remember the steps to wash their hands and choose healthy snacks